O Optimalisasi Pembelajaran Bahasa Arab Berbasis Kurikulum Merdeka dan Teori George C. Edward III di SMP-IT Al-Fauzan Bangkinang: Optimalisasi Pembelajaran Bahasa Arab Berbasis Kurikulum Merdeka dan Teori George C. Edward III di SMP-IT Al-Fauzan Bangkinang - Miftahul Jannatil Harvina; Nicky Bima Koni Ramadhan; Muhammad Fariz Aqila Aqila; Husnatul Hamidiyyah Siregar (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aims to analyze the optimization of Arabic language learning at Al-Fauzan IT Junior High School Bangkinang based on the Independent Curriculum and George C. Edward III management principles. The focus of the research lies in the development of adaptive, participatory, and contextual learning strategies through strengthening teacher-student communication, collaboration between students, and active involvement of schools and parents. The research uses a descriptive qualitative method with data collection through participatory observation, semi-structured interviews with school principals, teachers, students, and parents, as well as documentation of teaching modules, KOSP, and supporting facilities. The analysis was carried out thematically and triangulated the sources to ensure the validity of the findings. The results of the study show that the integration of the Independent Curriculum with Edward III's management principles makes Arabic learning more effective, innovative, and student-centered. Teachers act as facilitators who encourage active communication and collaborative practices, students experience improved language skills and confidence, while the involvement of schools and parents creates a conducive learning environment. These findings provide practical guidance for the development of contextual and collaborative Arabic learning strategies in modern Islamic boarding schools.